Facile one-pot synthesis of carbon incorporated three-dimensional hierarchical TiO2 nanostructure for highly efficient pollutant removal. Issue 103 (24th October 2016) - Xu, Shiping; Gao, Yuan; Sun, Xiang; Yue, Min; Yue, Qinyan; Gao, Baoyu
Abstract : The facile one-pot synthesized carbon incorporated 3D hierarchical TiO2 nanostructures simultaneously possessed superior adsorption capability and photocatalytic activity towards pollutants. Abstract : Herein, a carbon incorporated three-dimensional (3D) hierarchical TiO2 nanostructure (CRF -TiO2 ) was successfully synthesized via a facile one-pot route by coupling TiCl3 hydrolysis–oxidation with resorcinol–formaldehyde (RF) reaction without any surfactant. The fabricated CRF -TiO2 showed an interesting 3D hierarchical and mesoporous structure, possessed relatively large specific surface area and excellent light absorption capability, and the TiO2 in the final product was an anatase–rutile mixture with mature crystallinity. All of the above characteristics endow the prepared CRF -TiO2 with superior adsorption capability and photocatalytic activity compared to Degussa P25. As a result, with the presence of CRF -TiO2, pollutants in water could be rapidly separated from the aqueous phase via adsorption, which can ideally meet the requirements of fast water purification, and then the pollutants would be efficiently decomposed by a photocatalysis process under both UV and visible light irradiation to completely fulfill the pollutant removal target. The synthetic strategy for CRF -TiO2 employed in this study provides an effective solution for the synthesis of carbon incorporated 3D hierarchical TiO2 architectures, and can introduce new insights to design TiO2 -based photocatalysts for practical environmental purification applications.